Securitisation of terrorism in Indonesia - Wibisono, Ali Abdullah (2015)
This study explores the securitising move attempted by the government of President Megawati Sukarnoputri through the promulgation of Interim Laws 1/2002 and 2/2002 on Terrorism Crime Eradication and their stipulation as statutes in 2003 are examined in this study. This study also examines the discussion of the meaning of and appropriate responses to terrorism in Indonesia’s mainstream print media before (1998-2002) and after (2003-2010) with reference to the securitisation process. The goal of this thesis is to illustrate the continuing influence of the political meaning of terrorism on the articulated speech act of the government and the responses of the audiences.